Essay Quality in A Project-Based Learning: Case Study in EFL Writing Class at The Tertiary Level - Fitri Febrianti; Muamaroh Muamaroh (ITScience (Information Technology and Science), 2026)
Academic writing is one of the most challenging skills for EFL learners, requiring the integration of cognitive, linguistic, and organizational abilities. Project-Based Learning (PjBL) has been increasingly adopted as a pedagogical approach to support writing development; however, limited studies have examined the quality of student essays from a multi-dimensional perspective within PjBL contexts, particularly at the Indonesian tertiary level. This study aimed to evaluate the quality of essays produced by undergraduate EFL students in a PjBL writing class using five dimensions of writing quality: content, organization, vocabulary, language use, and mechanics. A qualitative case study design was employed involving 26 undergraduate students enrolled in a Standardized Test of Writing course at a private university in Surakarta, Central Java, Indonesia. Document analysis was used as the primary data collection technique. Students’ essays were assessed using the ESL Composition Profile developed by Jacobs et al. (1981), and the results were analyzed descriptively through frequency and percentage calculations. The findings revealed that 12 students (46.2%) were categorized as Good to Average and 14 students (53.8%) as Fair to Poor, with an overall mean score of 60.19 out of 100. Language use was the most challenging dimension, with 69.2% of students in the Fair to Poor category and the lowest mean percentage score (52.9%). Mechanics demonstrated the strongest performance, with 84.6% of students achieving Good to Average. Although PjBL provides meaningful writing engagement, students still require targeted instructional support in grammatical accuracy, idea development, and vocabulary use to improve overall essay quality.